PROFIL KOMPETENSI SOSIAL GURU-GURU DI LINGKUNGAN YAYASAN TAMAN PENDIDIKAN DAN SOSIAL NAHDLATUL ULAMA KHADIJAH DAN PENGARUHNYA TERHADAP KEPEKAAN SOSIAL SD KHADIJAH SURABAYA - Warsono; Mufidatus Shofiyah (Universitas Kanjuruhan Malang, 2019)
AbstractThe purpose of this study is to describe the social competency profile of elementary school teachers, describe the social sensitivity of elementary school students, describe the influence of social competence of teachers on the social sensitivity of elementary students in the Nahdlatul Ulama Education and Social Foundation (YTPS-NU) Khadijah Surabaya . The method in this study is descriptive quantitative, this type of research is non-experimental. The research samples were 60 teachers and 360 students. The results of this study describe; (1) There are differences in the level of social competence of teachers in YPTS-NU Khadijah Surabaya, namely SD Khadijah, on average 89.35; SD Khadijah 3 averaged 85.95 and SD Khadijah Pandegiling averaged 81.75, (2) There were differences in the level of social sensitivity of students in the YTPS-NU Khadijah school, SD Khadijah with an average of 82.46, SD Khadijah 3 with an average of 81.72, SD Khadijah Pandegiling with an average of 81.52, and there were differences in the level of social sensitivity of students in class III, IV, and V in three YTPS-NU Khadijah schools, the social sensitivity average of class III students was 79 , 18, the average social sensitivity of class IV students is 82.19 and the social sensitivity average of class V students is 84.33 and (4) There is a correlation of teacher social competencies towards students' social sensitivity, meaning that the higher the teacher's social competence, then the higher the social sensitivity of students, and the higher the level of the class, the higher the level of social sensitivity of students. abstrak Tujuan penelitian ini untuk mendiskripsikan tentang profil kompetensi sosial guru-guru SD, mendiskripsikan tentang kepekaan sosial siswa SD, mendiskripsikan tentang pengaruh kompetensi sosial guru-guru terhadap kepekaan sosial siswa SD di lingkungan Yayasan Taman Pendidikan dan Sosial Nahdlatul Ulama (YTPS-NU) Khadijah Surabaya. Metode dalam penelitian ini adalah deskriptif kuantitatif, jenis penelitian ini adalah non-eksperimen. Sampel penelitaian sebanyak 60 guru dan 360 siswa. Hasil penelitian ini mendeskripsikan; (1) Ada perbedaan tingkat kompetensi sosial guruguru di YPTS-NU Khadijah Surabaya yaitu SD Khadijah rata-rata 89,35; SD Khadijah 3 rata-rata 85,95 dan SD Khadijah Pandegiling rata-rata 81,75, (2) Ada perbedaan tingkat kepekaan sosial siswa di sekolah YTPS-NU Khadijah, SD Khadijah dengan rata-rata 82,46, SD Khadijah 3 denganrata-rata 81,72, SD Khadijah Pandegiling dengan rata-rata 81,52, dan ada perbedaan tingkat kepekaan sosial siswa kelas III, IV, dan V di tiga sekolah YTPS-NU Khadijah, rata-rata kepekaan sosial siswa kelas III adalah 79,18, rata-rata kepekaan sosial siswa kelas IV adalah 82,19 dan ratarata kepekaan sosial siswa kelas V adalah 84,33 dan (4) Terdapat korelasi kompetensi sosial guru terhadap kepekaan sosial siswa, artinya semakin tinggi kompetensi sosial guru, maka semakin tinggi kepekaan sosial siswa, dan semakin tinggi level kelas, maka semakin tinggi tingkat kepekaan sosial siswa.